Supporting entrepreneurial and income-generating activities of the returned IDPs in the Karabakh and East Zangezur regions - Gurbanlı, Fariz; Ibadov, Anar; Asadov, Mirzali (ADA University, 2023)
This study focuses on how individuals who have been internally displaced (IDPs) will return to their homelands which are areas affected by violence (Karabakh and East Zangezur regions). The study examines how this projected return will affect people as individuals, as groups, and as a whole from a socio-political standpoint. The setting is established in the beginning by emphasizing the importance of IDPs' returns in post-conflict situations. It underlines the need of comprehending the dynamics and difficulties of the return procedure itself. The study indicates that a variety of factors, such as security, infrastructure, livelihood possibilities such as employment , credits, financial supports, and social cohesiveness, frequently impact the decision to return. The study's conclusions shed insight on the intricate interplay of elements that affect a person's decision to go back. For IDPs considering a return, security issues, access to essential services, housing and legal procedures, economic opportunities, and social networks emerge as important factors. The report also emphasizes the necessity for comprehensive support systems to accommodate the unique needs of returning IDPs as well as the need of collaborative and community-based approaches in program formulation and implementation. After a conflict has ended, safety, peacebuilding, and long-term growth can all benefit from IDPs returning home and settling back in. However, obstacles including land disputes, asset restitution, social conflicts, and political dynamics need to be properly addressed to guarantee a peaceful and equitable return. This policy paper concludes with suggested policies meant to support the expected return of IDPs, and evaluation of those policies. The report underlines the necessity for a comprehensive and all encompassing strategy that considers the many needs and goals of returning IDPs.
Keywords: Internally displaced persons -- Repatriation -- Azerbaijan; Post-conflict reconstruction -- Azerbaijan; Resettlement -- Social and economic aspects -- Azerbaijan; Public and International Affairs